The Sensitivity of Family-Related Behaviors to Economic and Social Turbulence in Post-Socialist Countries, 1970-2010 - Sunnee Billingsley; Juho Härkönen; Maria Hornung (Comparative Population Studies, 2023)
Many demographic challenges and new trends have been observed across formerly state socialist countries after embarking on their political and economic transition. Including countries that range from Eastern Europe to Central Asia, this study explores whether some family-related events were more sensitive to the transformation that occurred in the 1990s than others, and whether the disruption was immediate or delayed across this wide range of contexts. Based on year-specific hazard ratios over four decades, results point to changes in fertility patterns being clearly linked to the transition. Second birth rates reacted almost immediately to societal disruption, whereas a more delayed change occurred for first births. Although abrupt changes in marriage and divorce rates also occurred, these changes often began before the transition and therefore may be part of longer-term developments. That second births were the most sensitive family event to the immediate change in conditions may be due to economic costs, but also unique characteristics related both to its lack of conferring a new social role on the individual, such as in the case of marriage and parenthood, and the narrower window of time in which this event usually occurs. The delayed changes in first births may instead reflect changes in norms and culture that influenced younger individuals when they reached childbearing ages.